"Of coronary arteries and men": the fight of a dialysis patient against his coronary arteries. (May 2014) - Vertolli, Ugo; Vinci, Claudio; Rebeschini, Mirca; Ruffatti, Annamaria; Scaparrotta, Giuseppe; Napodano, Massimo; Naso, Agostino; Calò, Lorenzo A.
Abstract Acute myocardial infarction (AMI) in dialysis patients is associated with high mortality rate. Large randomized controlled trials documenting the benefits of revascularization in the general population have excluded chronic dialysis patients. Few observational data suggest that revascularization may provide a survival benefit compared with medical treatment alone also in these patients. We report a case of a dialysis patient who survived five documented AMIs, underwent five coronary angiographies in 11 years, had several episodes of angina pectoris and underwent percutaneous transluminal coronary angioplasty (PTCA) with stenting and heart surgery for coronary bypassing. It represents a highly unusual therapeutic approach and might contribute to support also in dialysis patients the use of revascularization to improve survival.